DNMT1 represses p53 to maintain progenitor cell survival during pancreatic organogenesis - Georgia, Senta (Cold Spring Harbor Laboratory Press, 2013)
In the developing pancreas, self-renewal of progenitors and patterning of cell fates are coordinated to ensure the correct size and cellular makeup of the organ. How this coordination is achieved, however, is not clear. We report that deletion of DNA methyltransferase 1 (Dnmt1) in pancreatic progenitors results in agenesis of the pancreas due to apoptosis of progenitor cells. We show that DNMT1 is bound to the p53 regulatory region and that loss of Dnmt1 results in derepression of the p53 locus. Haploinsufficiency of p53 rescues progenitor cell survival and cellular makeup of the Dnmt1-deleted pancreas.